Penggunaan Data Mining Algoritma Apriori Pada Sistem Laporan Rincian Barang Persedian ATK Di Kantor Bpbd Pematangsiantar - Liwansen Hadomuan Damanik; Muhammad Rizky Wardana; Anju Vlaudya Sinaga (LPPM STIKOM Tunas Bangsa, 2021)
Pematangsiantar BPBD Office is one of the government agencies engaged in Regional Disaster Management where this agency must meet operational standards every day and be guided to make the right decisions in determining the purchase of disaster needs. By utilizing the purchase transaction data that has been stored in the goods purchase report or the entry of the number of items that have been reported by the secretary in the report. How to find out which items are purchased simultaneously, can be used association rule, which is a data mining technique to find rules association of a combination of items. The association search process uses the aid of a priori algorithm to generate pattern combinations of items and rules as knowledge and important information from purchase transaction data. The results of this study are in the form of an application to analyze spending patterns in which the resulting patterns can be used as recommendations in determining purchasing strategies by the Pematangsiantar BPBD Office.